2015
DOI: 10.1111/1541-4329.12048
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Augmented Reality Game to Teach Abstract Concepts in Food Chemistry

Abstract: One of the most pressing issues for many land grant institutions is the ever increasing cost to build and operate wet chemistry laboratories. A partial solution is to develop computer‐based teaching modules that take advantage of animation, web‐based or off‐campus learning experiences directed at engaging students’ creative experiences. We used the learning objectives of one of the most difficult topics in food chemistry, enzyme kinetics, to test this concept. Students are apprehensive of this subject and ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 19 publications
0
14
0
3
Order By: Relevance
“…Fourth, the majority of the studies included into this scoping review revealed the fact that although using AR applications in formal education is valuable for desired educational outcomes, technical thresholds (Crandall et al 2015;Lu, & Liu, 2015;Hsiao et al 2013) are recognized amongst one of the most critical boundaries for learning effectiveness. VaughanNichols (2009) stated that AR applications are spread into consumer settings more and the technology might be ready to become more commonplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the majority of the studies included into this scoping review revealed the fact that although using AR applications in formal education is valuable for desired educational outcomes, technical thresholds (Crandall et al 2015;Lu, & Liu, 2015;Hsiao et al 2013) are recognized amongst one of the most critical boundaries for learning effectiveness. VaughanNichols (2009) stated that AR applications are spread into consumer settings more and the technology might be ready to become more commonplace.…”
Section: Discussionmentioning
confidence: 99%
“…While the motivation or achievement of skill is recognized as an important reason for the development of teaching tools (Ferrer-Torregrosa et al, 2015), as in the case of AR applications, educators should also take consideration into the idea of how such applications might be integrated with instructional strategies or pedagogical approaches in formal education. Studies revealed that the use of AR in formal education might enable educators to combine those applications with various pedagogical approaches, such as, situated learning (Chang, & Jen-ch'iang, 2013;Chang, Wu, & Hsu, 2013;Crandall et al, 2015;Estapa, & Nadolny, 2015), inquiry-based learning (Wang et al, 2014;Bressler, & Bodzin, 2013;Chang, Wu, & Hsu, 2013), and game-based learning (Hwang et al 2015;Lu, & Liu, 2015;Bressler, & Bodzin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that there were several games [8,[23][24][25][26][27][28][29][30][31][32] that were referred to as AR games, but that were excluded from the final results because they did not satisfy my definition of AR. These games are essentially educational location-based mobile games based on the ARIS (Augmented Reality Interactive Storytelling) [33], ARLearn [8], or FreshAiR (http://www.playfreshair.com/) platforms, but their concept of AR is merely location-awareness without virtual content being augmented on top of a real-world view.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marker model single marker dipilih untuk penelitian ini dengan alasan lebih mudah, karena setiap objek makanan hanya membutuhkan satu marker yang sama. Teknologi AR di pilih sebagai media pembelajaran makanan tradisional karena mampu menampilkan informasi yang menarik, sekaligus berinteraksi langsung dengan objek 3D, sehingga terbentuk media pembelajaran yang interaktif dan edukatif [7].…”
Section: Pendahuluanunclassified